Aplikasi Segmentasi Pelanggan menggunakan Algoritma RFM/P dan Kmeans Clustering pada PT. XYZ - Priscilla Delaya; Andreas Handojo; Alexander Setiawan (Jurnal Infra, 2021)
Customers are one of the keys to the resilience of a business. Each customer has different behavior and needs, so they need different treatment. Intense competition in the retail business makes customers have many choices and can easily switch to other companies. As a solution for PT. XYZ to compete, a customer segmentation system is needed to help PT. XYZ understand and maintain their customer’s loyalty. Therefore, in this study, the RFM/P method was used to calculate customer value, which was then followed by Kmeans clustering to divide customers into three clusters, namely below zeroes, most growable customers, and most valuable customers for each product. The results of the questionnaire evaluation in system testing were carried out on 6 respondents, for application functionality 93% good, application design 90% good, ease of use of application 83% good, application responding to needs 90% good, and overall application 87% good.